Strategi Pengelolaan Destinasi Wisata Bukit Asah dan Pantai Pasir Putih di Desa Bugbug, Karangasem Tahun 2016 - 2023 - Hidayat Mahmudi; Ida Ayu Wirasmini Sidemen; Anak Agung Ayu Dewi Girindrawardani (JURNAL ILMIAH NUSANTARA, 2026)
This research is entitled "Management Strategy for the Bukit Asah and Pasir Putih Beach Tourist Destinations in Bugbug Village, Karangasem, 2016-2023". The Bugbug Traditional Village Tourism Development Agency (BP2DAB) was formed in 2016 with the aim of managing the Bukit Asah and Pasir Putih Beach Tourist Destinations. The problems raised in this research are: (1) Why are Bukit Asah and Pasir Putih Beach made into tourist destinations? (2) What is the Management Strategy for the Bukit Asah and Pasir Putih Beach Tourist Destinations? (3) What are the Implications of the Bukit Asah and Pasir Putih Beach Tourist Destinations for the socio-economics of the Bugbug Village community? This research aims to determine the development and implications for the community in Bugbug Village regarding the management of the Bukit Asah and Pasir Putih Beach tourist destinations. The methods in this research use heuristics, criticism, interpretation, and historiography. This research uses historical theory, management theory, and structural functional theory. These theories are used as a basis for answering the three research questions posed. The management of the Bukit Asah and Pasir Putih Beach tourist destinations is carried out in a planned manner through the establishment of the Bugbug Traditional Village Tourism Development Agency (BP2DAB) in 2016. The success of Bukit Asah and Pasir Putih Beach as tourist destinations in Bugbug Village is inseparable from the role of the Bugbug Traditional Village Tourism Development Agency (BP2DAB) as the managing agency. Natural and human resources factors contribute to Bukit Asah and Pasir Putih Beach's success as tourist destinations. The benefits to the community include job opportunities in the tourism sector and economic growth, as Bukit Asah and Pasir Putih Beach are village by village tourism.